Respuesta :

Answer:

The first transformation occurs when we add a constant d to the parent function \displaystyle f\left(x\right)={b}^{x}f(x)=b

x

, giving us a vertical shift d units in the same direction as the sign. For example, if we begin by graphing a parent function, \displaystyle f\left(x\right)={2}^{x}f(x)=2

x

, we can then graph two vertical shifts alongside it, using \displaystyle d=3d=3: the upward shift, \displaystyle g\left(x\right)={2}^{x}+3g(x)=2

x

+3 and the downward shift, \displaystyle h\left(x\right)={2}^{x}-3h(x)=2

x

−3. Both vertical shifts are shown in Figure 5.